Analisis Peran Bank Syariah Dalam Perekonomian Masyarakat: - Reni Ria Armayani Hasibuan; Imam Alfariqi; Ricky Pane; Serli Andiranti (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Abstract This study is intended to find out what work has been done by Islamic banks in the city of Binjai, and the extent to which people in the city of Binjai feel the impact of Islamic banks, especially in the monetary sector. The problem Islamic banks see is that people are used to ordinary financial foundations that have served the financial needs of the local area. The issue that is often discussed is the difference in the understanding of premiums in ordinary banks and benefits in Islamic banking. The results of this study can be concluded that Islamic banks are still classified as having less role in the economy of the special community in the city of Binjai, this is caused by the lack of effectiveness in maximizing the programs that have been designed so that people are still not familiar with the products and benefits of Islamic banks. As for this research using a quantitative methodology. This methodology withdraws from mathematical information, which is remembered for logical types, into a special examination that looks to clarify the state of each factor under study and the relationship between these factors. The consequence of the review shows that in its use, it is very noticeable that the types of goods that connect money with clients are very diverse and fluctuate. From these important items it is still possible to develop a variety of different items. Islamic banks have various kinds of income from profit sharing, rent, administrative costs, benefits, and profit sharing such as Shadaka, Infaq and Zakat. Through these halal products, Islamic banks provide extraordinary benefits to their customers. The relationship between Islamic banks and the benefits felt by clients through the use of sharia agreements can be seen that financial instruments and the progress of monetary business practice using contract standards that rely on Islamic sharia. Keywords: Role, Bank, Society, Customer, Sharia, Economy